Modelos de urnas e loterias - Oliveira, Paulo Roberto de (2014)
Many monthly, others weekly play in lottery games ignoring the randomness of the results, believing in luck or strategies that are sold to them in books about games. This monograph aims to show some concepts of probability and statistics unexplored in high school and also day to day situations that contain mathematical concepts of probability more accessible to this level of education showing some mathematical theories applied in practice games. Concepts will be discussed here: some probability distributions, their hope and variance, as well as lottery games and their probability calculations. Probability distributions will be calculated and listed in situations created from models of urns with two colors of balls, always having green as the color whose extraction will be considered successful and the red, whose extraction will be considered a failure. Now extractions with replacement balls will be made and sometimes extractions will be done without replacing them. Also, there is the case where new balls are added to both colors or one color.